Financial risks, monetary policy in the QE era, and regulation - Kouretas, Georgios P.; Papadopoulos, Athanasios P.; Tavlas, George S. (Journal of Financial Stability, 2022)
At the beginning of the present century, the literature on financial integration focused on the benefits of increased integration. In particular, the literature emphasized that a well-integrated financial system allows economic agents to engage in risk sharing while enhancing the smooth transmission of monetary policy. However, the international financial crisis of 2007-08 and the euro area sovereign debt crisis of 2009-15, brought to the fore the flip side of increased financial integration – namely, that higher financial integration among national jurisdictions creates the potential for destabilizing cross-country spillovers of capital flows. The papers in this Special Issue address financial system vulnerabilities in the aftermath of the 2007-08 financial crisis and the 2009-15 euro area crisis. In particular, the papers assess (1) vulnerabilities arising from such factors as the liberalization of financial systems, cross-country contagion, and climate change, and (2) policy responses, including macroprudential supervision and quantitative easing, to financial instabilities.